2014
DOI: 10.1155/2014/309631
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation Potential of Maná-Cubiu (Solanum sessiliflorumDunal) for the Deleterious Effects of Methylmercury on the Reproductive System of Rats

Abstract: Methylmercury, organic form of mercury, can increase the number of abnormal sperm and decrease sperm concentration and testosterone levels possibly due to the damage caused by reactive species to germ and Leydig cells. Maná-cubiu (Solanum sessiliflorum Dunal) is a native fruit from Amazon rich in iron, zinc, niacin, pectin, and citric acid, used in foods, beverages, and medicinal purposes, since it has been useful for treatment of various diseases caused by oxidative stress or nutritional deficiency. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
3
2
Order By: Relevance
“…These data are different from those of Frenedoso da Silva et al (2014) who observed histological alterations in testes of mouse exposed to MeHg (140 lg/kg, during 100 days) and from those of Pal and Ghosh (2012) who reported disorganization of cell plates and sinusoidal congestion in liver of rats treated with MeHg at 5 mg/kg for 15 days. These data are different from those of Frenedoso da Silva et al (2014) who observed histological alterations in testes of mouse exposed to MeHg (140 lg/kg, during 100 days) and from those of Pal and Ghosh (2012) who reported disorganization of cell plates and sinusoidal congestion in liver of rats treated with MeHg at 5 mg/kg for 15 days.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These data are different from those of Frenedoso da Silva et al (2014) who observed histological alterations in testes of mouse exposed to MeHg (140 lg/kg, during 100 days) and from those of Pal and Ghosh (2012) who reported disorganization of cell plates and sinusoidal congestion in liver of rats treated with MeHg at 5 mg/kg for 15 days. These data are different from those of Frenedoso da Silva et al (2014) who observed histological alterations in testes of mouse exposed to MeHg (140 lg/kg, during 100 days) and from those of Pal and Ghosh (2012) who reported disorganization of cell plates and sinusoidal congestion in liver of rats treated with MeHg at 5 mg/kg for 15 days.…”
Section: Discussioncontrasting
confidence: 99%
“…In the same way, no adverse effects were observed in histopathology of seminiferous epithelium, epididymis and liver of treated rats in both studied ages. These data are different from those of Frenedoso da Silva et al (2014) who observed histological alterations in testes of mouse exposed to MeHg (140 lg/kg, during 100 days) and from those of Pal and Ghosh (2012) who reported disorganization of cell plates and sinusoidal congestion in liver of rats treated with MeHg at 5 mg/kg for 15 days. These differences occurred probably due to the peculiarities of experimental design adopted in our study, including juvenile male rats together with the use of low doses.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, it was hypothesized that the consumption of Amazonian fruits would protect exposed populations, reducing the accumulation of mercury in humans [19]. Despite of that, studies with Amazonian fruits and MeHg intoxication are relatively scarce, being mainly limited to fruits such as guaraná, maná-cubiu, burití and açaí [20,21,22,23,24]. Although guaraná ( Paullinia cupana , Mart.)…”
Section: Introductionmentioning
confidence: 99%
“…However, maná-cubiu ( Solanum sessiliflorum Dunal), burití ( Mauritia flexuosa L.) and açaí ( Euterpe oleracea , Mart.) were already tested in rodent models of MeHg intoxication showing protection against the deleterious effects of the metal on reproductive system, memory acquisition and visual function, respectively [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The present findings show that P. glomerata exposure does not change body weight. Changes in body weight are indicative signs of systemic toxicity, and its reduction may be related to the effects of exposure to toxic substances (Clegg, Perreault, & Klinefelter, ; Frenedoso da Silva et al, ). Moreover, P. glomerata extract at a dose of 1,000 mg/kg, given directly via gavage, in the post‐natal period (Pnd1–Pnd15) with euthanasia at 70, decreased testis weights, possibly due to the toxic effects of the extract on this organ.…”
Section: Discussionmentioning
confidence: 99%